Fast Learners: One Trial Olfactory Learning in Insects - Adam, Elisabeth; Hansson, Bill S.; Knaden, Markus (Frontiers in Ecology and Evolution, 2022)
Despite their comparatively small brains, insects are able to survive and thrive in their environment. In the past, it was thought that insects are driven mainly by their instincts. However, today it is well established that they possess unique abilities to learn and use their experience in future decisions. Like many higher animals insects are able to acquire and retain information on when and where to forage, which mate to choose, where to lay their eggs and how to navigate in complex habitats. Learning can be surprisingly fast with only one single encounter with a suitable food source or oviposition site shaping an insect’s preference for up to a lifetime. In this review, we discuss the scope and limits of insect learning, focusing in specific on olfactory learning, and we raise the question whether currently used learning paradigms in artificial lab set-ups are able to answer all ecologically relevant questions.